Beta-Return Relationship in Up and Down Markets and Business Cycles - Peltomäki, Jarkko (My University, 2005)
The task of this thesis is to study the beta-return relationship in up and down markets and business cycles. This thesis uses two approaches to investigate this problem. An essential point is to study how this traditional beta is able to ex-plain returns in up- and down movements using two variables: GDP growth and market returns. The first approach is to measure and compare the explanatory power of the beta to market returns and business cycles. The second approach is to measure the linearity of the beta–return relationship compared with market returns and business cycles. To study the problem, four different kinds of methods are used: chi-square, mean tests, regression analyses and logistic regression. The data in-cludes returns of all stocks, GDP growth of Finland and the return indexes of the Finnish stock exchange. Over the period from January 1990 to December 1990 there is used the HEX All-Share Index. From January 1991 to December 2002 the HEX Portfolio Index is used. The result shows the magnitude of down market movements and GDP growth had an inverse relation to the performance of the CAPM. Non-linearity existed rather during down markets and positive GDP growth. However, the result is not significant. Despite of all, the most striking conclusion is that market return is a more explanatory variable than GDP growth to explain forms of the CAPM. This argues against risk models which reinforces the CAPM with economic variables, such as GDP growth.
Keywords: Beta-return relationship; the CAPM; business cycles; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|